Stres dengan Sistem Pembelajaran Online pada Mahasiswa di Era Pandemi COVID-19 - Padila Padila; Syufyan Rinaldi; Juli Andri; Harsismanto J; Muhammad Bagus Andrianto (Journal of Telenursing (JOTING), 2021)
This study aims to determine the relationship between stress levels and the online learning system for the Muhammadiyah Bengkulu University Nursing Study Program students during the COVID-19 pandemic. The research method was analyzed univariately by looking at the frequency distribution and bivariate analysis using the Kendal tau-b correlation test. The results showed a correlation between stress levels and the online learning system of 0.648 with a strong relationship and the direction of the positive correlation and the value of Sig. (2-tailed) of 0.000 < 0.005. In conclusion, there is a relationship between stress levels and online learning systems for the Bengkulu Muhammadiyah University Nursing Science Study Program students during the COVID-19 pandemic. Keywords: Students, COVID-19 Pandemic, Online Learning System, Stress Level